2017
DOI: 10.1177/2331216517706398
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition Outcomes After Cochlear Reimplantation Surgery

Abstract: This study compares speech recognition outcomes before and after cochlear reimplantation surgery, in relation to clinical factors known before and at time of surgery. Between 2006 and 2015, 2,055 adult cochlear implant surgeries were conducted at this center, of which 87 were reimplantation surgeries (4.2%). Speech recognition scores (SRS) assessed before and after reimplantation were available for 54 adults. Overall, SRS measured after reimplantation were similar to the best SRS obtained by the patient and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 28 publications
(46 reference statements)
5
36
0
5
Order By: Relevance
“…Although this finding considerably exceeded other reported revision rates [4,34], it illustrated the importance of interpreting results with respect to a relevant timeframe. According to our data, the mean time interval between Pri-CI and RCI was 6.6 years, comparable to results of other studies, which reported a mean length of device use before revision of 4.7-6 years [4,16,17,35]. Detailed examination for cases with a long follow-up period (≥10 years) revealed that 24% of the cases underwent RCI within the first 2 years after Pri-CI, 46% within a period of 2-10 years, and the remaining 30% after more than 10 years (Figure 2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although this finding considerably exceeded other reported revision rates [4,34], it illustrated the importance of interpreting results with respect to a relevant timeframe. According to our data, the mean time interval between Pri-CI and RCI was 6.6 years, comparable to results of other studies, which reported a mean length of device use before revision of 4.7-6 years [4,16,17,35]. Detailed examination for cases with a long follow-up period (≥10 years) revealed that 24% of the cases underwent RCI within the first 2 years after Pri-CI, 46% within a period of 2-10 years, and the remaining 30% after more than 10 years (Figure 2).…”
Section: Discussionsupporting
confidence: 89%
“…Although declined performance has a profound impact on patients' communication skills and, consequently, on their quality of life, it has received minor attention in the literature and tends to be overlooked in revision studies. With regard to studies that applied a clinical criterion for evaluating a change in performance post-RCI, Reis et al (2017) [17] as well as Mahtani et al (2014) [18] used a criterion of ≥10% change in speech recognition scores for different sentence tests, and reported declined performance in 15.8% and 8% of the RCIs, respectively. Rivas et el.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear reimplantation (CR) has been shown to be a safe procedure with outcomes comparable to initial CI performance [Reis et al, 2017]. Revision surgery can be typically elaborate and also accompanied by local pathological changes like middle-ear inflammation/infection, CO after otic capsule violation, and the exposure of ana-Audiol Neurotol 2020;25:323-335 DOI: 10.1159/000507419 tomical structures that puts them at risk.…”
Section: Revision Surgerymentioning
confidence: 99%
“…Due to increased awareness about the benefits of cochlear implantation and recipients living longer following implantation, the prevalence of reimplantation is increasing. Reis, Boisvert, Looi, and da Cruz (2017) report on speech recognition outcomes before and after cochlear reimplantation to assess the safety and success of this type of surgery. Another study explores the potential benefits of bilateral over unilateral cochlear implants ( Rana et al., 2017 ), demonstrating that both speech comprehension and spatial release from masking are improved in bilaterally implanted adults.…”
Section: Overview Of Special Issuementioning
confidence: 99%